Allogeneic stem cell transplantation in fully MHC-matched Mauritian cynomolgus macaques recapitulates diverse human clinical outcomes. Issue 1 (December 2017) - Burwitz, Benjamin; Wu, Helen; Abdulhaqq, Shaheed; Shriver-Munsch, Christine; Swanson, Tonya; Legasse, Alfred; Hammond, Katherine; Junell, Stephanie; Reed, Jason; Bimber, Benjamin; Greene, Justin; Webb, Gabriela; et al.
Abstract Allogeneic hematopoietic stem cell transplantation (HSCT) is a critically important therapy for hematological malignancies, inborn errors of metabolism, and immunodeficiency disorders, yet complications such as graft-vs.-host disease (GvHD) limit survival. Development of anti-GvHD therapies that do not adversely affect susceptibility to infection or graft-vs.-tumor immunity are hampered by the lack of a physiologically relevant, preclinical model of allogeneic HSCT. Here we show a spectrum of diverse clinical HSCT outcomes including primary and secondary graft failure, lethal GvHD, and stable, disease-free full donor engraftment using reduced intensity conditioning and mobilized peripheral blood HSCT in unrelated, fully MHC-matched Mauritian-origin cynomolgus macaques. Anti-GvHD prophylaxis of tacrolimus, post-transplant cyclophosphamide, and CD28 blockade induces multi-lineage, full donor chimerism and recipient-specific tolerance while maintaining pathogen-specific immunity. These results establish a new preclinical allogeneic HSCT model for evaluation of GvHD prophylaxis and next-generation HSCT-mediated therapies for solid organ tolerance, cure of non-malignant hematological disease, and HIV reservoir clearance. Rhesus macaques are not ideal for studying response to allogeneic hematopoietic stem cell transplant (allo-HSCT) owing to complex MHC genetics that prevent full MHC-matching. Here the authors show that inbred Mauritian-origin cynomolgus macaques are a superior preclinical model of allogeneic stem cell transplantation that mimics diverse clinical outcomes of human allo-HSCT.